Comparative release profile of sustained release matrix tablets of verapamil HCl - Mathur, Vikas; Nagpal, Kalpana; Singh, Shailendra Kumar; Mishra, Dina Nath (International Journal of Pharmaceutical Investigation, 2013)
Introduction: Verapamil hydrochloride (VH) is a calcium channel blocking agent used in the treatment of hypertension, cardiac arrhythmia and angina pectoris. The short half‑life and high frequency of administration of VH makes it a suitable candidate for designing sustained drug delivery system. The aim of the present investigation was to develop a sustained release matrix tablet of verapamil hydrochloride (VH) using ethyl cellulose, methyl cellulose, Eudragit RS 100, hydroxypropyl methylcellulose and carboxymethyl cellulose and to evaluate the drug release kinetics. Materials and Methods: In order to achieve the required sustained release profile, the tablets were prepared by a wet granulation method using avicel PH 101 and magnesium stearate as binder and lubricant, respectively. Results: The formulated tablets were characterized for pre‑compression and post‑compression parameters and they were in the acceptable limits. The drug release data obtained after an in vitro dissolution study was fitted to various release kinetic models in order to evaluate the release mechanism and kinetics. The criterion for selecting the best fit model was linearity (coefficient of correlation). Drug release mechanism was found to follow a complex mixture of diffusion, swelling and erosion. Furthermore, to minimize the initial burst drug release, batches were coated by using Eudragit RS100 polymer. After coating the tablets, a better release profile of the formulated tablets was expected and the release rate of the drug was compared with the marketed SR tablet of VH. Conclusion: The dosage form holds the potential to control the release rate of drug and extend the duration of action of a drug.
Keywords: Ethyl cellulose; eudragit RS 100; hydroxypropyl methylcellulose; matrix tablet; methyl cellulose; verapamil HCL